Peran Orang Tua Dalam Mengembangkan Perilaku Sosial Pada Anak Usia Dini - Khusnul Khotimah (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2015)
Abstract: early childhood education can not be separated from the role of parents who are first and foremost educators before children get other’s education. One important element in the prosess of early childhood education in order to develop his perdonality is the development of a child’s social behavior.successful parentingwill result in good personal adulthood and vice versa. The things parents do to foster the social behavior of childern is to provide opportunities for children to find peers and create a group that aims to respect the freinds activity, increased a strong desire to be accepted as a member of a group, and will feel happy along wits his friends. Parents conduct surveillance to monitor and control the child so that the relationship between parent and child entwined in harmony. Parent also provide apportunities for children to play. The formation of social behavior of children in the home is also done through an increase in moral judgment of children by parents based on freedom, equelity, and mutual acceptance. Parents teach discipline to the children to behave morally acceptable group. Furthemore, parents also taugh to have good language skills, because with good language of children tend to accepted and respected by freinds.